Kaposi Sarcoma in Afghanistan: A Case Series from a Tertiary Referral Center - Alyssa D. Higgins; Richard J. Dunn; Omer Malikzai; Mirwais Ahmadzai; Jerad M. Gardner; Benjamin K. Stoff; Josette R. McMichael (MDPI AG, 2022)
Kaposi sarcoma is a vascular endothelial neoplasm caused by human herpesvirus 8. Although it is a well-studied disease, little is known about the specific characteristics or epidemiology of Kaposi sarcoma in Afghanistan. The data consist primarily of anecdotal reports and epidemiological studies extrapolated from neighboring countries. In this case series, we summarize existing data about Kaposi sarcoma in Afghanistan and present seven histologically confirmed cases with associated clinical features to shed light on the characteristics of Kaposi sarcoma in this unique geographic setting.